Effects of aerobic and resistance exercise on patients with hypertension: a systematic review and meta-analysis focusing on the sympathetic nervous system - Wang, Jing-feng; Mao, Su-jie; Xia, Fan; Li, Xiao-lin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTreatment and control of hypertension are important for the prevention of cardiovascular diseases. The autonomic nervous system plays a major role in the development and progression of hypertension and has become a new research hotspot in cardiovascular disease. Exercise as a non-pharmacologic intervention has likewise received much attention in the field of cardiovascular disease.ObjectiveTo determine the effects of exercise on the sympathetic and parasympathetic nervous systems of hypertensive patients. The effects of aerobic, resistance, and combined aerobic and resistance exercise on autonomic function in hypertensive patients will be compared and analyzed to explore more appropriate exercise modalities for hypertensive patients.MethodsDatabases such as Web of Science, PubMed, Embase, Cochrane Library, and CNKI were searched to collect randomized controlled trials (RCTs) evaluating exercise (aerobic, resistance, and aerobic combined with resistance exercise) as an intervention for the autonomic nervous system in hypertension. The Cochrane evaluation tool and Jadad scale were used to evaluate the methodological quality of the included literature. RevMan software was used for statistical and sensitivity analyses, and Stata software was used for net analysis and assessment of publication bias.ResultsThis study included 20 studies with 794 hypertensive patients. Exercise improved the joint effect sizes of the basic phenotype in hypertensive patients [SMD = 0.89, 95% CI (0.69, 1.10)] as well as blood pressure variability in hypertensive patients [WMD = 0.89, 95% CI (0.51, 1.27)]. The effect of exercise on hypertensive patients was more centered on the sympathetic nervous system [SMD = 0.29, 95% CI (0.17, 0.40)] and was not significant on the parasympathetic nervous system in hypertensive patients [SMD = −0.08, 95% CI (−0.31, 0.14)]. In addition, the efficacy of aerobic combined resistance exercise on the regulation of blood pressure and the autonomic nervous system in hypertensive patients was the most significant (p < 0.05).ConclusionThe regulation of exercise in hypertensive patients is dominated by the sympathetic nervous system. The efficacy of aerobic combined resistance exercise on the autonomic nervous system of hypertensive patients is particularly prominent and plays an important role in improving the blood pressure level of patients, among other things.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025634362.